2023
DOI: 10.1227/neu.0000000000002462
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review Comparing Focused Ultrasound Surgery With Radiosurgery for Essential Tremor

Abstract: BACKGROUND: Focused ultrasound (FUS-T) and stereotactic radiosurgery thalamotomy (SRS-T) targeting the ventral intermediate nucleus are effective incisionless surgeries for essential tremor (ET). However, their efficacy for tremor reduction and, importantly, adverse event incidence have not been directly compared. OBJECTIVE: To present a comprehensive systematic review with network meta-analysis examining both efficacy and adverse events (AEs) of FUS-T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 73 publications
1
6
0
Order By: Relevance
“…We successfully targeted and ablated the VIM nucleus of the thalamus, resulting in expected clinical outcomes that are comparable to those seen with RF, GKRS, and MRIg-FUS thalamotomies. 9,10,23 In our study, we observed an 83.37% reduction in tremor at Data are number of patients. Transient AEs were those that appeared during or after the thalamotomy procedure and vanished within a month.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…We successfully targeted and ablated the VIM nucleus of the thalamus, resulting in expected clinical outcomes that are comparable to those seen with RF, GKRS, and MRIg-FUS thalamotomies. 9,10,23 In our study, we observed an 83.37% reduction in tremor at Data are number of patients. Transient AEs were those that appeared during or after the thalamotomy procedure and vanished within a month.…”
Section: Discussionsupporting
confidence: 53%
“…7,8 Alternative lesional brain surgery procedures, such as thalamotomy using radiofrequency (RF), gamma-knife radiosurgery (GKRS), or magnetic resonance imaging-guided focused ultrasound (MRIg-FUS), have been shown to be efficacious to manage tremor symptoms in individuals for whom DBS is unsuitable. 5,9,10 Recently, a novel technology has emerged in the field of lesional brain surgery, known as MRI-guided laser interstitial thermal therapy (MRIg-LITT). 11 MRIg-LITT has been shown to be effective and safe in management of brain tumors and seizure disorders.…”
mentioning
confidence: 99%
“…During the past decade and aiming at the same surgical target, HIFU has been suggested as an appealing procedure, producing a controlled thermocoagulation, with an immediate clinical effect [ 12 ]. A recent systematic review compared the results of HIFU and SRS for ET [ 21 ]. The authors found similar efficacy between the two techniques, with a trend towards higher efficacy yet greater adverse events incidence with HIFU [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review compared the results of HIFU and SRS for ET [ 21 ]. The authors found similar efficacy between the two techniques, with a trend towards higher efficacy yet greater adverse events incidence with HIFU [ 21 ]. It was concluded that smaller lesion volumes could mitigate FUS-T off-target effects for greater safety [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation